First principles study of mechanical, thermal, electronic, optical and superconducting properties of C40-type germanide-based MGe2 (M = V, Nb and Ta) - M.H. Kabir; M.M. Hossain; M.A. Ali; M.M. Uddin; M.L. Ali; M.Z. Hasan; A. K. M. A Islam; S.H. Naqib (Results in Physics, 2023)
Non-centrosymmetric germanide-based superconductors have recently attracted particular attention because of their unconventional physical properties. In the present study, we comprehensively investigated the structural and hitherto unexplored electronic, optical, mechanical, thermal, and superconducting state properties of germanide-based superconductors, MGe2 (M = V, Nb, and Ta), using the density functional theory. The obtained lattice parameters and accordingly the volume of the unit cells agree very well with the earlier reported values, indicating the high reliability of the physical properties studied. All the compounds studied herein are dynamically and mechanically stable. The compounds are brittle (ranked: NbGe2 < VGe2 < TaGe2) and elastically anisotropic in nature.The estimated hardness values of MGe2 (M = V, Nb and Ta) are found to be 16.95, 14.96 and 19.6 GPa, respectively. Different optical functions (dielectric functions, reflectivity, absorption coefficient, photoconductivity, refractive index and loss function) and thermal properties (thermal conductivity, thermal expansion coefficient, Debye temperature, specific heat and melting point) are investigated.The reflectance spectra in the visible and near UV region were found to be >50% for all these compounds, demonstrating their potential for application as coating material to reduce heating from incident electromagnetic radiation. Based on the results obtained for thermal properties and comparison with benchmark system, Y4Al12O9 and some other predicted compounds, the titled compounds could also be used as thermal barrier coating materials. Some important parameters for the understanding of the superconducting behavior, such as the Coulomb pseudopotential, London penetration depth, coherence depth, Debye temperature, electron-phonon coupling constant, and Ginzburg-Landau parameter, are also estimated, and the results obtained support that the NbGe2and TaGe2 compounds should be categorized as a type-2 superconductors.